A Decision Support Tool for Sustainable Land Use, Transportation, Buildings/Infrastructure, and Materials Management - Hall, Eric S. (Am J Environ Engineer, 2017)
One issue for community groups, local and regional planners, and politicians, is that they require relevant information to develop programs and initiatives for incorporating sustainability principles into their physical infrastructure, operations, and decision-making processes. This research project addressed the issue through two research questions. The first research question that this project was designed to address, which was greatly influenced by the vast number of references in the sustainability literature, was an ontological one, “what are the major categories that sustainability decisions can be grouped under, and how might those categories be related?”. The second research question that this project answered was, “how can information contained in the sustainability literature be made accessible to users in a convenient format?”. The Multi-Sector Sustainability Browser (MSSB) is a decision support tool (DST) designed to synthesize and summarize research in four sustainability decision domains, Land Use, Buildings and Infrastructure, Transportation, and Materials Management in a manner that provides easy and rapid access to information for use in planning and decision making. Weblinks are provided to reference documents and resources from the four sustainability decision domains, allowing users to download relevant documents and extract information in support of sustainability decisions and related program initiatives.